Makna Keuntungan Penjual Salome (Studi Fenomenologi Hermeneutik) - Wahyu Junaedi; Chairun Nisa; Indah Nurfazlillah; Silviana Gunarsih; Titik Rodiyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Salome seller profession is an alternative entrepreneurship for the community because the business is quite easy to do. This study aims to find the meaning of profit perceived by Salome sellers. Salome sellers who are able to survive long enough in pursuing their profession certainly have their own awareness in interpreting the benefits they get during selling Salome. This research was conducted on salome sellers who have pursued their profession for more than 10 years using a hermeneutic phenomenology approach. The results showed that salome sellers interpreted its advantages in terms of broad market segments, light business capital, and business management flexibility. The findings of the research's significance can also be taken into consideration in terms of measuring the risk of salome business performance from strategic, financial, and operational aspects. Keywords: The Meaning of Profit, Hermeneutic Phenomenology, Risk of Business Performance